2021
DOI: 10.1037/xan0000275
|View full text |Cite
|
Sign up to set email alerts
|

Latent inhibition in young children: A developmental effect?

Abstract: Previous research by Kaniel & Lubow in 1986 found that young children (aged 4 -5 years) exhibited poorer learning (latent inhibition) to preexposed stimuli than older children (aged 7-10 years). The aim of our research was to develop a computer-based, child-friendly study that would replicate and extend the work of Kaniel & Lubow in a way that ruled out other, attention-based explanations of their effect. One hundred and four children and 32 undergraduate students took part in our experiment. This consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The results indicated that children who did not receive MAH AND HASELGROVE preexposure (Group NPe) required fewer trials to meet criterion in the training stage than children in the Pe-M group, but not the Pe-NM group. Thus, whether latent inhibition was observed in these 10-to 11-year-olds depended upon the conditions of the preexposure stage: in the absence of a masking task preexposure did not slow later learning-in keeping with the results of the older children tested in Kaniel and Lubow (1986) and McLaren et al (2021). However, when preexposure was conducted in the context of a concurrent masking task then learning was subsequently attenuatedlatent inhibition was observed in older children.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The results indicated that children who did not receive MAH AND HASELGROVE preexposure (Group NPe) required fewer trials to meet criterion in the training stage than children in the Pe-M group, but not the Pe-NM group. Thus, whether latent inhibition was observed in these 10-to 11-year-olds depended upon the conditions of the preexposure stage: in the absence of a masking task preexposure did not slow later learning-in keeping with the results of the older children tested in Kaniel and Lubow (1986) and McLaren et al (2021). However, when preexposure was conducted in the context of a concurrent masking task then learning was subsequently attenuatedlatent inhibition was observed in older children.…”
supporting
confidence: 67%
“…It is therefore difficult to explain slower RTs to the preexposed cue in terms of either learned inattention/irrelevance or general response inhibition (cf., Lubow et al, 1976;McLaren et al, 2021). Finally, unlike early studies of the development of latent inhibition in children, with this procedure the effect of preexposure is investigated within subjects (McLaren et al, 2021), permitting a single measure of latent inhibition to be derived to serve in developmental trajectory analysis. Kaniel and Lubow (1986, p. 367) state that the main purpose of their studies was "to generate a developmental curve for latent inhibition," and the goal of the current study is the same.…”
mentioning
confidence: 99%
“…Responding on the keyboard sometime during the game should be expected by the participants as such an expectation was set up in the instructions and practice trials. As suggested by McLaren et al (2021), when stimuli are presented in a situation where making responses could be expected, pre-exposure might engage a response inhibition mechanism. Goal trackers, who are better able at inhibiting responding, may be learning to actively inhibit the response in the presence of the light better than sign trackers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most basic assumptions of all theories of perceptual learning is that simple exposure to a stimulus can result in reduced processing of that stimulus and that this would be revealed in a demonstrable latent inhibition effect. R. McLaren et al (2021) present evidence for a retardation in learning to a stimulus following preexposure to that stimulus in young children (4 -5 years old). It is important to note that this effect of latent inhibition is not found in older children (7-10 years old) or in adults.…”
mentioning
confidence: 86%